2014
DOI: 10.3390/v6020683
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Host Factors to Treat West Nile and Dengue Viral Infections

Abstract: West Nile (WNV) and Dengue (DENV) viruses are major arboviral human pathogens belonging to the genus Flavivirus. At the current time, there are no approved prophylactics (e.g., vaccines) or specific therapeutics available to prevent or treat human infections by these pathogens. Due to their minimal genome, these viruses require many host molecules for their replication and this offers a therapeutic avenue wherein host factors can be exploited as treatment targets. Since several host factors appear to be shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 158 publications
0
70
0
1
Order By: Relevance
“…Moreover, both NS3 and NS5 were implicated in DHF as they were found to be the immunodominant T-cell antigens compared to other viral proteins (Duangchinda et al, 2010). Hence, NS5 has long been considered an attractive drug target due to its multiple crucial roles in viral replication (Dong et al, 2008), and its cellular interaction partners may also reveal new therapeutic avenues for fatal DHF or DSS (Krishnan & Garcia-Blanco, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both NS3 and NS5 were implicated in DHF as they were found to be the immunodominant T-cell antigens compared to other viral proteins (Duangchinda et al, 2010). Hence, NS5 has long been considered an attractive drug target due to its multiple crucial roles in viral replication (Dong et al, 2008), and its cellular interaction partners may also reveal new therapeutic avenues for fatal DHF or DSS (Krishnan & Garcia-Blanco, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Flaviviral Y2H studies conducted by different groups have, thus far, shown a curious lack of overlap in their datasets. For example, Khadka et al (2011) and Le Breton et al (2011) both generated DENV NS5 interaction networks, with no overlapping data (Krishnan & Garcia-Blanco, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses of this family that infect humans are a significant cause of morbidity and mortality worldwide and include dengue virus (DENV), West Nile virus (WNV), yellow fever virus (YFV), and the recently emerging pathogen Zika virus (ZIKV) (1)(2)(3)(4). Due their relatively small genome (10 to 11 kb), flaviviruses are highly dependent on the host cell to complete their life cycle, and many aspects of the host-pathogen interface still remain to be elucidated (5)(6)(7). Research into the host functions supporting and limiting flaviviral replication both informs our understanding of the host-pathogen interface as well as provides promising avenues toward the discovery of antiviral therapeutics.…”
mentioning
confidence: 99%
“…Other countermeasures include repurposing drug screens of FDA-approved 'orphan' drugs that targets ZIKV infection are under research [83] or viral proteins that need oligomerization has appeared as a potent strategy. Anti-viral drugs directed against flavirus infection or cell-intrinsic defense might also be monitored.…”
Section: Zikv Treatment Strategiesmentioning
confidence: 99%